Qualification of Acts in the Context of Insignificance: Theoretical and Practical Issues - Irina G. Ragozina; Vladislav V. Brazhnikov (Сибирское юридическое обозрение, 2016)
The article deals with the qualification of insignificance of act problematic issues, the impact of judicial discretion in the formation of judicial practice on the assessment of insignificance is reflected. The basic signs of insignificance are described, the conditions for recognition insignificant acts are defined. The authors come to the conclusion to exclude part 2 of Art. 14 of the Criminal Code of the Russian Federation and amend it by the article "Exemption from the criminal liability in connection with acts of insignificance", limiting the range of categories of such acts only to minor offenses committed by first time.